Detection, fate and transport of the biohazardous agent Toxoplasma gondii in soil water systems: Influence of soil physicochemical properties, water chemistry and surfactant - Kinsey, Erin N.; Korte, Caroline; Gouasmia, Sohib; L'Ollivier, Coralie; Dubey, Jitender P.; Dumètre, Aurélien; Darnault, Christophe J.G. (Environmental microbiology reports, 2023)
A series of laboratory experiments were conducted to study the fate and transport of Toxoplasma gondii oocysts in soils as a function of soil physicochemical properties and soil water chemistry properties. Soil columns were homogeneously packed with loamy sand soils (Lewiston and Greenson series) and sandy loam soils (Sparta and Gilford series), and subject to hydrologic conditions characterized by the absence and presence of an anionic surfactant—Aerosol 22 in the artificial rainfall. Quantitative polymerase chain reaction (qPCR) was utilized for the detection and enumeration of oocysts in soil leachates to evaluate their breakthrough and in soil matrices to examine their spatial distribution. Differences in the rate and extent of transport of oocysts were observed as a function of physical and chemical parameters tested. The breakthrough of oocysts was observed for all the soils irrespective of the presence of surfactant. However, in the absence of surfactant, the predominant fate of oocysts in soils subject to simulated rainfall was their retention in the soil profile. The presence of surfactant induced a change in the fate of oocysts in these soils exposed to rainfall simulation as the predominant fate of oocysts was found to be in the soil leachates. Laboratory set‐up for flow‐through experiments of soil columns under rainfall simulator in a biosafety cabinet; Photomicrograph of Toxoplasma gondii oocysts; Photos of soil column and soil column section; Breakthrough curves of oocysts in soils (oocysts (C/Co) vs. pore volume, where Co is the concentration of oocysts in the inoculums applied to the surface of the soil columns, and C refers to the concentration of oocysts in leachates of the soil columns); Distribution profiles of oocysts in soils (number of oocysts per gram of dry soil vs. depth of soil).